1998
DOI: 10.1016/0168-8278(88)80010-2
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-type matrix metalloproteinase-1(MT1-MMP) gene is overexpressed in highly invasive hepatocellular carcinomas

Abstract: The present study showed that the MT1-MMP gene is strongly expressed in hepatocellular carcinoma cells and is involved in the invasion potential of hepatocellular carcinoma, and also that MT1-MMP may be one of the key molecules responsible for the invasion potential of hepatocellular carcinoma. Furthermore, the evidence suggests that MT1-MMP and MMP-2 cooperate in the process of cancer invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…Harada et al and Arii et al have demonstrated that MT1-MMP is involved in hepatocarcinoma cell migration (29,30); however, the molecular mechanism is unknown. In searching for the underlying mechanism of α1-PDX inhibition of the migration and invasion of MG-63 and Saos-2 osteosarcoma cells in the present study, the expression levels of MT1-MMP mRNA and protein in MG-63 and Saos-2 osteosarcoma cells upon α1-PDX treatment were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Harada et al and Arii et al have demonstrated that MT1-MMP is involved in hepatocarcinoma cell migration (29,30); however, the molecular mechanism is unknown. In searching for the underlying mechanism of α1-PDX inhibition of the migration and invasion of MG-63 and Saos-2 osteosarcoma cells in the present study, the expression levels of MT1-MMP mRNA and protein in MG-63 and Saos-2 osteosarcoma cells upon α1-PDX treatment were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of MT1 -MMP has enhanced pulmonary metastasis in animal models (Tsunezuka et al, 1996) and the invasiveness of MDCK cells in other experiments (Hotary et al, 2000). Expression of MT1 -MMP is associated with invasion and/or metastasis of human cancers (Harada et al, 1998;Kikuchi et al, 2001;Mimori et al, 2001;Shimada et al, 2000), and it also plays a role in cell motility mediated by CD44-shedding (Kajita et al, 2001). It is noteworthy that Claudin-1, Laminin-5 g2 and CD44 are also up-regulated by the b-catenin/Tcf4 complex Hlubek et al, 2001;Wielenga et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of the TPs described herein are detected in solid and hematologic tumors (Table 1) (Ueno et al, 1997;Afzal et al, 1998;Harada et al, 1998;Kitagawa et al, 1998;Curran and Murray, 1999;Ellerbrock and Stack, 1999;Ishigaki et al, 1999;Brinckerhoff et al, 2000;Ellenrieder et al, 2000;Neal et al, 2000;Antczak et al, 2001a, b;Fillmore et al, 2001;Kerkela et al, 2001;Soderstrom et al, 2001;Hashida et al, 2002;Mishima et al, 2002;Seiki and Yana, 2003). In some cases, malignancy is associated with a marked increase in TP expression, whereas in others it is associated with downregulation.…”
Section: Cancermentioning
confidence: 99%